Labile Organic Carbon Fractions, Regulator of CO2 Emission: Effect of Plant Residues and Water Regimes. Issue 10 (22nd July 2016) - Hassan, Waseem; Bashir, Safdar; Ahmed, Niaz; Tanveer, Mohsin; Shah, Adnan Noor; Bano, Rizwana; David, Julie
Abstract : The soil organic carbon (C) pool is the largest among the terrestrial C pools, and plays a vital role in the exchange of CO2 . The increase in CO2 emission from soil to atmosphere has raised concerns about potential global warming. The current study was conducted with the objectives to investigate the relationship between labile organic C fractions and CO2 fluxes in an Alfisol soil treated with green manure (GM) and wheat straw (WS), and moisture regimes namely, W1 (50%) and W2 (100%). The incorporation of GM and WS increased ( p < 0.05) the CO2 emission and labile C fractions under both water regimes. The CO2 fluxes showed positive correlation with all measured soil labile organic C fractions, i.e ., total organic carbon (TOC), light fraction of organic carbon (LFOC), particulate organic carbon (POC), easily oxidizable carbon (EOC), dissolved organic carbon (DOC), microbial biomass carbon (MBC), reducing sugar carbon (RSC), and readily mineralizable carbon (RMC). The overall effect of labile C fractions on the CO2 emission was in the order LFOC > POC > EOC > DOC > MBC > RSC > RMC > TOC. The results demonstrated that LFOC, POC, EOC, DOC, MBC, RSC, and RMC had higher effects on CO2 fluxes as compared to TOC. The LFOC was more suitable and sensitive indicator than POC, EOC, DOC, MBC, WSC, RMC, and RSC for CO2 emissions and change in the soil organic C status. Abstract : Soil organic carbon (SOC) fractions have significant influence on CO2 fluxes. Among them, the labile organic C fraction, particularly the light fraction of organic carbon (LFOC) is of utmost importance and plays a vital role in governing the CO2 emission from soil to atmosphere. Moreover, the labile organic C fraction is a more suitable indicator to predict the overall status of soil C.